Accelerated weathering resistance of high-density polyethylene composites reinforced with microcrystalline cellulose and fire retardants - Dönmez Çavdar, A.; Dizman Tomak, Eylem; Boran, Torun, S.; Arpaci, S.S. (Elsevier Ltd, 2021)
In this study, high-density polyethylene (HDPE) composites reinforced with microcrystalline cellulose (MCC) and fire retardants, ammonium zeolite (AZ) and mono ammonium phosphate (MAP) were exposed to ultraviolet (UV) radiation using an accelerated weathering test chamber for total of 672 h. The weathering effects on the surface characterization and morphology of the composites were examined with Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), color, gloss and surface roughness measurements. Furthermore, tensile and flexural tests were determined after the weathering exposure. The results showed that the weathering of composites led to changes on the investigated properties. As a result of surface roughness measurement, the highest Rz (mean peak-to-valley height) values were obtained from the composite surfaces of the HDPE/AZ10 (86/10, w/w) and the HDPE/MCC/MAP10 (71/15/10, w/w). The SEM studies confirmed that AZ addition resulted in some protrusion at the composite surfaces while MAP addition caused some coarsening on the composite surfaces. After the weathering, the decrease in mechanical strengths of the samples was found as 32%. The overall mechanical properties were not considerably affected with 672 h of the weathering exposure. © 2021 Elsevier Ltd
Keywords: Accelerated weathering; Color change; Composites; Fire retardants; HDPE; MCC